Analisis Pengaruh Motivasi, Pelatihan dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT Multi Data Palembang - Agung Indriansyah (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
Job satisfaction and job motivation are directly related to staff performance. Job satisfaction and job motivation experienced by staff could reduce or increase staff performace. Staff who feels satisfied with the job obtained will be motivated to increase his/her performace, consequently it will impact on improving the company performance overall. This research was done at the Indonesia based PT Multi Data Palembang. The aim of the research is to investigate the effect of staff performace relation to the job satisfaction and job motivation that has been moderated by job duration. The samples number determined in this research are 30 respondents and used sampling purposive method. As independent variables are job satisfaction and job motivation, and its variable moderating is job duration, while its dependent variable is staff performance. The results of the analysis is using moderated regression are the job Motivation Variable, job Training variable and job satisfaction are positively influenced to staff performance, and the job duration variable moderated job satisfaction to the staff performance, meanwhile job duration variable did not succeed to moderate job motivation to staff performance.The result of the analysis could be known that 22 percent variation of staff performance could be explained by independent variable and moderating variable that has been examined in this research and 78 percent by the other factors outside the model.